(untitled) (Journal of Human Sciences, 2021)
Germa (Jarma) occupied an excellent position, which could be a link between the north and south of the continent, and with Egypt, as it was a center for the reception and distribution of Mediterranean and African products. This is what the archaeological missions and exploratory projects, whether Italian or English have made clear, and they showed the contradiction and the great error, in which the classic sources fell, when they described the Garamantes, as the barbarian people, who have no civilization and do not accept the other, and his image is an enemy of the Mediterranean civilization. But these archaeological missions, and clarified the extent of civilization progress that the capital enjoyed, and how it adapted in the middle of the desert, and produced a pure Libyan civilization, which was in contact with the surrounding civilizations, whether in the north, south or east.